2015
DOI: 10.1002/dev.21385
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal stress and early‐life exposure to fluoxetine have enduring effects on anxiety and hippocampal BDNF gene expression in adult male offspring

Abstract: With the growing use of selective serotonin reuptake inhibitor medications (SSRIs) for the treatment of depression during the perinatal period, questions have been raised about the longterm impact of these medications on development. We aimed to investigate how developmental SSRI exposure may alter affect-related behaviors and associated molecular processes in offspring using a rodent model of maternal stress and depression. For this purpose, prenatally stressed or non-stressed male offspring were exposed to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 96 publications
3
46
0
Order By: Relevance
“…The serotonin system consists of 15 different receptors that are key players at crucial neurodevelopmental stages, regulating neurogenesis, apoptosis, axon branching and dendritogenesis 11 . Many of the studies included in the synthesis of evidence in the current review, which have been selected on the presence of behavioral outcomes, also include outcomes reflecting brain health from the global to the molecular level: the corticosterone response to stress 74, 81, 96, 100, 123, 124, 126, 130, 135 , brain structure and connectivity 71, 77, 84, 93, 101, 110, 122 , neuronal health 59, 82, 85, 89, 104, 109, 111, 126, 135 , monoamine concentrations in the brain 43, 44, 46, 59, 105, 116, 117, 133, 135, 140, 141 , protein expression in the brain – mainly related to the serotonergic system and neurogenesis 62, 71, 78, 88, 91, 97, 127, 129, 141 , gene expression 76, 94, 96, 112, 113, 120, 121, 123, 137, 141, 143 , and epigenetic modifications 76, 112, 114, 124 .…”
Section: Discussionmentioning
confidence: 99%
“…The serotonin system consists of 15 different receptors that are key players at crucial neurodevelopmental stages, regulating neurogenesis, apoptosis, axon branching and dendritogenesis 11 . Many of the studies included in the synthesis of evidence in the current review, which have been selected on the presence of behavioral outcomes, also include outcomes reflecting brain health from the global to the molecular level: the corticosterone response to stress 74, 81, 96, 100, 123, 124, 126, 130, 135 , brain structure and connectivity 71, 77, 84, 93, 101, 110, 122 , neuronal health 59, 82, 85, 89, 104, 109, 111, 126, 135 , monoamine concentrations in the brain 43, 44, 46, 59, 105, 116, 117, 133, 135, 140, 141 , protein expression in the brain – mainly related to the serotonergic system and neurogenesis 62, 71, 78, 88, 91, 97, 127, 129, 141 , gene expression 76, 94, 96, 112, 113, 120, 121, 123, 137, 141, 143 , and epigenetic modifications 76, 112, 114, 124 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, maternal postpartum FLX can impact development of female endocrine physiology which could alter hippocampal plasticity. It should be noted that different studies using a lower dose of FLX (5 mg/kg; s.c.) in dams found that maternal postpartum FLX has no effect on density of DCX-expressing cells in males or females at weaning [56], in adolescence [17], or in adulthood ([58]; only males examined). This suggests that only higher doses of FLX alter density of DCX-expressing cells in pre-adolescent offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Our data contribute to the body of work elucidating the numerous relationships between air pollutant exposure during pregnancy and mental disorders, including anxiety (Perera et al, 2012). Maternal environmental stressors such as stress itself, testosterone, and lipopolysaccharides enhanced anxiety-like behavior of offspring (Boulle et al, 2015;Hu et al, 2015;Solati et al, 2015). The maternal environment is very important in the development of the offspring, as several "critical periods" of central nervous system development occur during gestation.…”
Section: Discussionmentioning
confidence: 68%